Evaluation of success rate of laparoscopic castration without orchidectomy in 32 mature horses. (11th November 2013) - de, C.; Geffroy, O.; Siliart, B.; Albaric, O.; Tessier, C.
Summary The surgical success of laparoscopic castration without orchidectomy results from avascular necrosis of the testes. However, failures and subsequent production of testosterone and stallion‐like behaviour have been previously identified. Laparoscopic castration without removal of the testes was performed in 32 horses with 2 normal descended scrotal testes between July 2006 and October 2012. The objectives of our study were to evaluate the success rate of laparoscopic castration without orchidectomy on descended testes in our population and assess complications and recovery time. Endocrine tests were performed after surgery and owners also asked to report on their horse's behaviour and ability to resume exercise. Castration was deemed successful if endocrine test results were in accordance with gelding values. Failed horses were castrated using a conventional technique and histology performed when possible. Basal testosterone levels decreased below 3 nmol/l after surgery in 30/32 cases. However, in 2 horses, stallion behaviour persisted and histological evaluation after inguinal castration showed residual viable tissue. Two horses maintained high testosterone levels after surgery associated with stallion‐like behaviour. Based on these results, 12.5% of horses (4/32 horses) failed to be considered a gelding based on either endocrine tests and/or histology. All horses, with one exception, were able to resume exercise less than a week after the procedure. Laparoscopic castration without orchidectomy appears to be a safe procedure. When assessing the success of laparoscopic castration, our total failure rate was 12.5% (4/32 horses) which is significantly higher than previously reported.